Dendrites issues and advances in Zn anode for aqueous rechargeable Zn‐based batteries. Issue 3 (25th June 2020) - Li, Qing; Zhao, Yuwei; Mo, Funian; Wang, Donghong; Yang, Qi; Huang, Zhaodong; Liang, Guojin; Chen, Ao; Zhi, Chunyi
Abstract: Rechargeable Zn‐based batteries (RZBs) have attracted much attention and been regarded as one of the most promising candidates for next‐generation energy storage featured with high safety, low costs, environmental friendliness, and satisfactory energy density. The aqueous electrolyte system exhibits great potential to power the future wearable electronics. Apart from the achievements of high capacity cathode and stable electrolyte, the anode suffers from problems of dendrite growth, hydrogen evolution, and passivation with limited attention. The dendrite formation strongly restricts the battery lifespan. Therefore, strategies focused on dendrite suppression are carefully categorized and summarized in this review, including crystallographic orientation manipulation, electric field control, ion flux regulation, and mechanical shield. Each strategy and the detailed approaches are critically dissected. Finally, remaining challenges are emphasized in this review, expecting to supply further research with potential directions to fulfill the high performance of the Zn anodes. Abstract : Dendrites issues in aqueous rechargeable Zn‐based battery have aroused increasing attention recently. This review categorized from the main fundamental theory in suppression the zinc dendrites including crystallographic orientation manipulation, electric field control, ion flux regulation, and mechanical shield. Detail approaches under each category are discussed critically and further considerations are provided for future study.